2019
DOI: 10.1055/a-0733-7086
|View full text |Cite
|
Sign up to set email alerts
|

Linked color imaging improves the endoscopic visibility of gastric mucosal cancers

Abstract: Background and study aims  As a newly developed endoscopy technique, linked color imaging (LCI) provides very bright images with enhanced color tones. With the objective of improving the detection rate of gastric mucosal cancers, which are often difficult to detect, we examined the utility of LCI from the viewpoint of visibility. Patients and methods  The current study used 100 consecutive gastric mucosal cancers ≤ 20 mm in diameter. For each lesion, we selected one endoscopic image acquired by white-light im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Compared to WLI, LCI particularly enhanced the visibility of a normochromic, flat, and depressed lesion, which contributes to the early detection of gastric mucosal cancer [3]. Therefore, RGB pixel brightness as a potential way to improve the accuracy of EGC screening is an additional benefit to LCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to WLI, LCI particularly enhanced the visibility of a normochromic, flat, and depressed lesion, which contributes to the early detection of gastric mucosal cancer [3]. Therefore, RGB pixel brightness as a potential way to improve the accuracy of EGC screening is an additional benefit to LCI.…”
Section: Discussionmentioning
confidence: 99%
“…The LCI observation mode is one of the four modes offered by the IEE system. The main feature is color enhancement that makes it easier to recognize the slight difference in mucosal color [3]. For instance, lesions with HP infection were identified with a diffusion of red color [4].…”
Section: Background and Aimsmentioning
confidence: 99%
“…O UR PREVIOUS STUDY showed that LCI improved the visibility of EGC in general, according to the subjective visibility scale. 24 In the current study, we evaluated the efficacy of LCI for detecting EGC after eradication, which are more difficult to detect compared to EGC in general. When using the same visibility scales, a similar result was obtained for EGC after eradication.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopists scored the lesions based on a previously reported four-point visibility scale. 15,24,28 With respect to the objective analyses, we evaluated the color difference (CD) of each lesion on WLI and LCI images using the Commission Internationale d'Eclairage (CIE) L*a*b* color space and delta ELab formulas. This was done using commercially available image analysis software (Adobe Photoshop; Adobe Systems, San Jose, CA, USA).…”
Section: Visibility Of Egc After H Pylori Eradicationmentioning
confidence: 99%
See 1 more Smart Citation